2021
DOI: 10.3390/cancers13215572
|View full text |Cite
|
Sign up to set email alerts
|

Letermovir Prophylaxis and Cytomegalovirus Reactivation in Adult Hematopoietic Cell Transplant Recipients with and without Acute Graft Versus Host Disease

Abstract: Cytomegalovirus (CMV) is the most clinically significant infection after allogeneic hematopoietic-cell transplantation (allo-HCT) and is associated with increased mortality. The risk for CMV reactivation increases with graft versus host disease (GVHD). GVHD contributes to significant morbidity and mortality and is treated with immunosuppressive therapies that can further increase CMV infection risk. Prophylaxis with letermovir, an oral antiviral approved to prevent CMV, has been shown to decrease the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“… 23 , 24 , 25 , 26 The decrease in csCMVi in period 2 compared with that in period 1 was thus explained by the use of letermovir in patients receiving corticosteroids, almost all for aGVHD, which is known to be a major factor in CMV infection. 27 , 28 , 29 , 30 At the same time, we found an important beneficial of letermovir in patients at high risk in csCMVi prevention with an improved and nearly statistically significant OS through 1 year after transplantation. It seems thus reasonable to assume that a larger number of patients would have allowed for reaching statistical significance.…”
Section: Discussionsupporting
confidence: 62%
“… 23 , 24 , 25 , 26 The decrease in csCMVi in period 2 compared with that in period 1 was thus explained by the use of letermovir in patients receiving corticosteroids, almost all for aGVHD, which is known to be a major factor in CMV infection. 27 , 28 , 29 , 30 At the same time, we found an important beneficial of letermovir in patients at high risk in csCMVi prevention with an improved and nearly statistically significant OS through 1 year after transplantation. It seems thus reasonable to assume that a larger number of patients would have allowed for reaching statistical significance.…”
Section: Discussionsupporting
confidence: 62%
“…Ganciclovir or foscarnet must be initiated early in those with CMV reactivation to avoid clinical manifestations and disease. Letermovir is approved for CMV prophylaxis for up to 100 days after alloHCT 195 , although letermovir prophylaxis can be used after day 100 in patients at high risk of late CMV infection, including those with acute GVHD who are receiving immunosuppressive treatement 196 . Importantly, letermovir is not effective for prevention of varicella zoster virus infection, and patients must continue to receive valacyclovir to prevent shingles and chicken pox 197,198 .…”
Section: Primermentioning
confidence: 99%
“…Consistent with the Phase III clinical trial, 13 most studies showed an increased rate of CMV DNAemia/pp65 antigenemia, including csCMV‐I, after interrupting LMV prophylaxis. Risk factors for post‐LMV CMV DNAemia included umbilical cord blood transplants and antithymocyte globulin, 78 haploidentical allo‐SCT with posttransplant cyclophosphamide, 56,63,78,82 GvHD, 53,75 donor CMV‐negative serostatus, 75 and use of mycophenolate mofetil for aGvHD prophylaxis 56 . Most of these conditions could be regarded as surrogate markers of poor anti‐CMV specific T‐cell reconstitution and may provide a rationale to extend LMV prophylaxis; in this sense, a Phase III randomized clinical trial exploring the benefit of extending LVM prophylaxis beyond Day 200 (http://Clinicaltrials.gov: NCT03930615) replicated the results of the original trial 13 by reducing csCMV‐I during LMV prophylaxis (2.8% in the LMV group vs. 18.9% in the placebo group); however, a comparable incidence of csCMV‐I across groups was observed at 48 weeks after stopping LMV (14.6% in the LMV group vs. 20.3% in the placebo group) 83 .…”
Section: Efficacy Of Lmv In Preventing Active CMV Infection and End‐o...mentioning
confidence: 99%
“…There is solid evidence for the clinical efficacy of primary prophylaxis (also secondary) with LMV in preventing csCMV‐I and CMV end‐organ disease in adult CMV seropositive allo‐SCT patients and, to a much lesser extent, in pediatric patients, both in randomized trials and in a real‐life setting 13,48–81 . A comprehensive review and meta‐analysis on this subject was recently published 14 .…”
Section: Efficacy Of Lmv In Preventing Active CMV Infection and End‐o...mentioning
confidence: 99%
See 1 more Smart Citation